Global warming, vulnerability and policy implications for Malaysia - Salleh, K.O. (2009)
The Intergovernmental Panel for Climate Change (IPCC) report on the “Science of Climate Change” in 2007 states that the Southeast Asia Region experienced a small increase in temperature (~ 0.3 oC ) and rainfall (~ 3%) for the last decade or so, however, there is general agreement amongst scientists that the changing behavioural patterns of the el-Nino ENSO , Monsoons and to a certain extent the Indian Dipole Oscillation circulation systems are triggering weather extremes and variability to influence changing behavioural patterns of hydro-meteorological and geomorphological events within the major river basins (for example, floods, droughts,haze pollution, slope failures and the emergence of certain diseases) in the country. In addition to these events, Malaysia are already exposed to increasing threats (directly or indirectly) from Low Pressure Oceanic Cells (LPOC’s) that develops in the South Indian Ocean (tropical storms and cyclones) and the Pacific – South China Sea Regions (tropical storms and typhoons). These events life cycles are thought to be governed by the increasing warming of ocean surface waters as a result of the global warming – climate change effect. Changing hydro-meteorological and geomorphological processes have increased in intensity, frequency and impacts to make Malaysia more aware and vigilant to the potential threat of global warming climate change and the need for effective solutions. To this date the impact of these changes can still be absorbed by the strong foundations of Malaysia’s environmental management programmes and backed by stringent economic policies including effective poverty eradication and food production programs. However, it must be understood here that the environmental policies addresses only the environmental change threat and not specifically the climate change threat where in the long term the impact scenario would generally diverge, and the resilience of Malaysia to the climate change threat would generally decrease and her vulnerability increases. This scenario can change if the gradual increase in global warming is left unchecked and unabated because increasing global temperatures could lead to thresholds been breached where habitats and ecosystems could not recover to existing equilibrium and stable conditions. Climate change could well trigger national and international distributional conflicts and intensify problems already hard to manage in the region (inter and intra regional conflicts). Malaysia could be affected in future conflict scenarios as a result of climate change. Four conflict constellations can be identified in which critical developments can be anticipated as a result of climate change impact on Malaysia. These are, conflict constellations on (1) climate-induced degradation of marine and freshwater resources, (2) climate-induced decline in food production capacities and other environmentally driven economic systems, (3) climate-induced increase in certain hydro-meteorological and geomorphological events and (4) climate change ethical – justice issues such as environmentally induced displacements and migration and the deprivation and sustenance of certain livelihood activities. The social impacts of climate change will vary in the different parts of Malaysia. “Security risks associated with climate change”, shows selected hotspots can be identified. The existence of these climate change conflict constellations threaten to overstretch the established national- regional - global governance system, thus jeopardizing international stability and regional security. The last half decade had witnessed a number of threatening environmental events that are climate change induced. These events will steadily intensify and exacerbates existing environmental risks and have serious repercussions on Malaysia. Climate extremes, variability and anomalies will threaten the bases of many of the country’s populace livelihoods and her major economic systems, especially vulnerable are the poor and those living at the threshold of the poverty line. The low income economic systems are especially vulnerable as their practices are dictated and sustained by climate – weather behavioral patterns. Any changes to these behavioral patterns would seriously affects the daily practices and livelihoods of highland farmers, traditional fishing and agriculture practices of coastal regions, and other forms of rural cottage industries. Malaysia’s large scale economic systems such as agriculture, fishing, hydro-electric power generation and tourism related activities are also vulnerable to climate variabilities and extremes as these industries to a major extent are environmentally driven. Climate change will hit Malaysia hard. Timely adaptation measures should therefore be an integral element of her national policies. However, like most developing countries, Malaysia lacks the skills and capacities to implement effective adaptation measures at all levels of systems been threatened. Moreover, the impacts of climate change will increase the vulnerability of weak and the more fragile systems and further reduce their adaptive capacities. The nature of vulnerability and resilience of these systems to the climate change threat needs to be assessed and understood. There’s not much that Malaysia can do in mitigating and curtailing green house gases emission, where her role lies mainly to provide a powerful voice in support of global efforts in green house gases reduction and mitigation, however there’s much that can be done in order to reduce vulnerability and resilience of her populace and livelihood systems. In general it can be said that the greater the warming, the greater the security risks to be anticipated, and Malaysia needs to adapt to these impending risks. The objectives of this paper is to discuss, (1) the importance and significance of global warming and climate change as emerging security issues (2) the application of a theoretical framework for climate insecurity – vulnerability study, to examine (3) the potential stresses of global warming – climate change on regional environmental systems dynamics and potential security risks hotspots, (4), the potential “critical” systems that would be seriously affected and why these systems are vulnerable, (5)) the adaptation, mitigation and future policy implications of Malaysia to address the climate change threat.